Serum Proinsulin in Bangladeshi Subjects with Impaired Glucose Tolerance (Bangladesh Journal of Medical Biochemistry, 2015)
Hyperproinsulinemia is commonly present in subjects with impaired glucose tolerance. The present study was undertaken to investigate the proinsulin level in Bangladeshi IGT subjects and to explore its association with insulin resistance. This observational study was conducted under a case-control design with IGT subjects (n=50) and controls (n=44). IGT was diagnosed following the WHO Study Group Criteria. Serum glucose was measured by glucose-oxidase method, serum lipid profile by enzymatic method and serum insulin and serum proinsulin were measured by ELISA method. Insulin secretory capacity (HOMA%B) and insulin sensitivity (HOMA%S) were calculated from fasting serum glucose and fasting serum insulin by homeostasis model assessment. The study subjects were age- and BMI- matched. Mean (±SD) age (yrs) of the control and IGT subjects were 40±6 and 40±5 respectively (p=0.853). Mean (±SD) BMI of the control and IGT subjects were 23±3 and 22±2 respectively (p=0.123). Fasting glucose was not significantly higher in IGT subjects, but serum glucose 2 hours after 75 gm glucose load was significantly higher in IGT subjects. Median (Range) value of fasting serum glucose (mmol/l) of control and IGT subjects were 5.3 (3.8-6) and 5.2 (4-12) respectively; (p=0.297). Median (Range) value of serum glucose (mmol/l) 2 hours after 75 gm glucose load of control and IGT subjects were 6.1 (3-7.8) and 7.9 (5- 21) respectively; (p=0.001). Fasting TG was significantly higher in IGT subjects and LDL-c was significantly lower in IGT subjects. Serum Total cholesterol and HDL-c were not significantly different between the IGT and control subjects. Median (Range) value of fasting serum TG (mg/dl) of control and IGT subjects were 119 (51-474) and 178 (82-540) respectively; (p=0.001). Median (Range) value of fasting serum T chol (mg/dl) of control and IGT subjects were 180 (65-272) and 186 (140-400) respectively; (p=0.191). Median (Range) value of fasting serum HDL-C (mg/dl) of control and IGT subjects were 29 (19-45) and 31 (15-78) respectively; (p=0.914). Median (Range) value of fasting serum LDL-C (mg/dl) of control and IGT subjects were 117(29-201) and 111(41- 320) respectively; (p=0.001). Fasting serum proinsulin was significantly higher in IGT subjects. Median (Range) value of fasting serum proinsulin (pmol/l) of control and IGT subjects were 9.2(1.8-156) and 17(3-51) respectively; (p=0.001). Insulin secretory capacity (HOMA%B) was higher but insulin sensitivity (HOMA%S) was significantly lower in case of IGT subjects. Median (Range) value of HOMA%B of control and IGT subjects were 97(46-498) and 164(17-300) respectively; (p=0.001). Median (Range) value of HOMA%S of control and IGT subjects were 68(19-270) and 39(15-110) respectively (p=0.001). In multiple regression analysis a significant negative association was found between fasting proinsulin and insulin sensitivity (p=0.037). The data led to the following conclusions: a) Insulin resistance is the predominant defect in Bangladeshi IGT subjects. b) Basal proinsulin level is significantly increased in IGT subjects. c) Insulin resistance is negatively associated with serum proinsulin in IGT subjects. DOI: http://dx.doi.org/10.3329/bjmb.v7i2.22411 Bangladesh J Med Biochem 2014; 7(2): 41-46